Energetic and respective part of lactic and aerobic sources over a giant slalom in young ski racers - Hintzy, F.; Grenier, J.; Coulmy, N. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The energy cost of a giant slalom event was previously measured by Saibene et al. (1985) and Veicteinas et al. (1985) during exercise and during recovery from a complete lap, tacking into account the blood lactate and the oxygen consumption. The actual main criticism is the disrespect of the real skiing conditions (Douglass bag method, VO2 not continuously measured, sport equipment..). The purpose of this study was then to quantify the total net energetic output and the part of both aerobic and lactic sources in alpine skiing over a giant slalom in young ski racers; then to estimate the influence of the biological maturation on these parameters. Seven minor ski racers aged in average (±SD) 14,0 ± 0,5 years were investigated and divided in two groups according to the gender or the biologic stages of maturation. They performed both a giant slalom in a field study and a incremental test (to determine the maximal aerobic capability). The oxygen consumption was measured breath to breath with an automatic gas analyzer system (Cosmed K4b², Rome, Italy) during the whole giant slalom and the blood lactate concentration was calculated before and 2 min after the slalom in order to respectively determine both aerobic and lactic energy sources. Average (±SD) V02, lactate and total net energetic output were respectively 44.8% VO2peak, 5.7 mmol.l-1 and 33,3 ± 6,6 kJ.min-1 with important inter-individual variations. The relative part of lactic and aerobic sources averaged 28.4% and 71.6%, respectively. The more advanced biologic maturation of some subjects tends to increase the participation of the lactic source. Present results showed low energy expenditure during a giant slalom in young racers, which increases with the subject`s biologic maturation.